Blodig skam - Gjerde, Una Mathiesen (K&K - Kultur og Klasse, 2018)
Since Aristotle’s time, menstruation has been a stigmatised bodily fluid. It has been a source of shame and guilt for women for centuries. In this article, I focus on how Scandinavian artists since the 1970’s have contributed to make menstruation public through menstrual art. There is wide diversity within Scandinavian menstrual art. Some artists address the menstrual stigma directly in their work, while others use the semiotic and symbolic power of menstrual blood – as abject – to provoke and raise political awareness on feminist issues. I focus on menstrual art in relation to notions of shame and guilt. I argue that menstrual art has contributed to reducing destructive menstrual shame amongst Scandinavian women, even though this may not have been the artists’ main intention in creating the work. Even though the menstrual stigma has been reduced drastically – especially the last five years – menstrual shame has not disappeared. Thus, menstrual art can still contribute to reducing and preventing women from feeling ashamed of their periods. As long as half of humanity menstruates one-third of their life time, the menstrual discussion and menstrual art will remain topics of interest and importance.